Effect of marble tile waste powder (MTWP) filler on cure and mechanical behaviour of natural rubber (NR) compound / Nor Mazlina Abdul Wahab ... [et al.] - Abdul Wahab, Nor Mazlina; Azman, Aztikah; Majid, Noor Aishatun; Syed Ismail, Sharifah Nafisah; Mustafa, Mohd Syamaizar (Universiti Teknologi MARA, Perlis, 2019)
As part of the increasing effort to reutilize of residue generated from industrial activities, an attempt has been made to utilize marble tile waste as a potential filler in natural rubber (NR) composite when low strength applications are required. In the experimental part, 10 µm size of marble tile waste powder (MTWP), with five different loadings up to 40 parts per hundred of rubber (phr) were used in NR composites to study the effect of MTWP loading on the cure characteristics and mechanical properties. The addition of MTWP as filler resulted in shorter cure time and scorch time which is preferable in rubber processing. It also enhanced the properties of tensile modulus and hardness while tensile strength, elongation at break and swelling ratio decreased with increasing MTWP loading. This study thus shows that MTWP can be used as economical alternative filler in NR compound and has potential as a partial replacement of reinforcing filler like carbon black in various rubber products.